2013
DOI: 10.1128/jb.00418-13
|View full text |Cite
|
Sign up to set email alerts
|

DR1769, a Protein with N-Terminal Beta Propeller Repeats and a Low-Complexity Hydrophilic Tail, Plays a Role in Desiccation Tolerance of Deinococcus radiodurans

Abstract: The Deinococcus radiodurans genome encodes five putative quinoproteins. Among these, the ⌬dr2518 and ⌬dr1769 mutants became sensitive to gamma radiation. DR2518 with beta propeller repeats in the C-terminal domain was characterized as a radiation-responsive serine/threonine protein kinase in this bacterium. DR1769 contains beta propeller repeats at the N terminus, while its C-terminal domain is a proline-rich disordered structure and constitutes a low-complexity hydrophilic region with aliphatic-proline dipept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Escherichia coli recombinant strain cultures were induced with IPTG at a final optimal concentration of 0.1 mM for 4 h, and the cells were desiccated and treated with H 2 O 2 as previously described (Rajpurohit and Misra, ; Jiang et al ., ; Wang et al ., ). Different serial dilutions of these cells were plated onto LB agar plates and incubated at 37°C for 1 day before colonies were observed and counted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Escherichia coli recombinant strain cultures were induced with IPTG at a final optimal concentration of 0.1 mM for 4 h, and the cells were desiccated and treated with H 2 O 2 as previously described (Rajpurohit and Misra, ; Jiang et al ., ; Wang et al ., ). Different serial dilutions of these cells were plated onto LB agar plates and incubated at 37°C for 1 day before colonies were observed and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Both desiccation and oxidation are widely studied extreme processes that are detrimental to the growth of organisms because they induce protein aggregation and nucleic acid damage (Rajpurohit and Misra, ; Atashgahi et al ., ). Moreover, recent advancements have shown that the organismal responses to both stresses are similar, indicating that the mechanisms for protecting crucial biomolecules from damage are related (Fredrickson et al ., ; Chakrabortee et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 50 species of the Deinococcus genus have been identified in a variety of environments18. Deinococcus are distinguished by their extraordinary tolerance to a number of lethal agents including ionizing radiation, hydrogen peroxide, osmotic pressure, desiccation, UV radiation and mitomycin C (MMC)19202122. It is widely accepted that efficient DNA repair systems and cell defence systems including an unusual cell envelope and small molecule antioxidants (e.g.…”
mentioning
confidence: 99%
“…Among these eight proteins, DR_1998/KatE1 and DR_A0259/KatE2 are the two catalases that exhibit activity in D. radiodurans (75), and DR_A0202/SodC is a Cu/Zn-dependent superoxide dismutase that catalyzes the conversion of metabolic superoxide (O 2 − ) radicals to H 2 O 2 (Lim et al, 2019). Of the remaining five proteins, DR_1769 is a conserved protein present in all Deinococcus species with a regulatory role in resistance to desiccation and gamma radiation (Rajpurohit and Misra, 2013;Lim et al, 2019). DR_1736 is a nuclease involved in DNA repair, which processes DNA to generate 3' overhang fragments for the further recombination with near homologous fragments (Kota and Misra, 2013).…”
Section: Qpr6 Affects the Transport Of Catalases To The Periplasmmentioning
confidence: 99%